2018
DOI: 10.5539/ijel.v8n3p270
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogy of English Idioms: An Etymological Perspective

Abstract: In EFL context, there is a considerable shift from single word lexical items to phraseology. Idioms constitute a core part in the phraseology block of the language. Idioms, in spite of their variety and cultural roots, are one of the most neglected areas in EFL perspective. Non-native learners of English as a foreign language do not feel motivated to use idiomatic resources of the language creatively. It is also a fact that pedagogy of idioms to EFL learners has been a challenging task for non-native teachers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…With English as a lingua franca (ELF), and people around the world learning English as a second or foreign language (ESL/EFL), English learners encounter English idioms frequently. Because of the “multidimensionality” of English idioms, they play an essential role and have received great attention recently, especially in EFL research (Qureshi et al, 2018). However, non-native speakers usually have difficulty understanding idioms, even though they may have a large vocabulary, because the meaning of English idioms goes beyond literal meanings (Liontas, 2003; Xie, 2017), so that the meaning of idioms often can’t be decoded by interpreting the individual words (Khonbi & Sadeghi, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…With English as a lingua franca (ELF), and people around the world learning English as a second or foreign language (ESL/EFL), English learners encounter English idioms frequently. Because of the “multidimensionality” of English idioms, they play an essential role and have received great attention recently, especially in EFL research (Qureshi et al, 2018). However, non-native speakers usually have difficulty understanding idioms, even though they may have a large vocabulary, because the meaning of English idioms goes beyond literal meanings (Liontas, 2003; Xie, 2017), so that the meaning of idioms often can’t be decoded by interpreting the individual words (Khonbi & Sadeghi, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The importance of learning idioms for classroom practices has been studied by Qureshi et al (2018) and the study revealed the EFL idioms presented with etymological background make a lasting impact on the overall comprehension of language. Orfan (2020) highlighted a better understanding of idioms is a requirement for English proficiency and accuracy despite some challenges in learning idioms in classroom context.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, investigating systemic variation types of modified idioms in journalism context has not been reported in the literature. No collection of modified idioms has been recorded as previous research focused on the purpose of pedagogy (Anwar, Tahir & Qureshi, 2018). Such an investigation will indeed provide insight in understanding the use of modified idioms and study frequency of modified idioms will indicate a degree of familiarity.…”
Section: Introductionmentioning
confidence: 99%